2016
DOI: 10.1590/1678-457x.0086
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different drying parameters on color, β-carotene, antioxidant activity and minerals of apricot (Prunus armeniacaL.)

Abstract: Apricot is one of the fruits dried by using different methods, such as sun, convective or microwave drying. The effects of drying methods on the components of this fruit differ depending upon the temperature or time parameters. In this research, the impacts of convective, microwave and microwave-convective drying techniques on color, β-carotene, minerals and antioxidant activity of apricots were investigated. The color values (L*, b*, ΔE ab, h° and C* ab ) of dried fruit were decreased, while the a* values inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 59 publications
5
32
0
1
Order By: Relevance
“…This behavior is similar to that observed on TPC and TFC. The results concerning antioxidant capacity in the current study are comparable to previous findings by İncedayi, Tamer, Sinir, Suna, and Çopur (2016) in apricots affected by a higher temperature and power level treatments caused less inhibition on DPPH radical.…”
Section: Determination Of Antioxidant Capacitysupporting
confidence: 91%
“…This behavior is similar to that observed on TPC and TFC. The results concerning antioxidant capacity in the current study are comparable to previous findings by İncedayi, Tamer, Sinir, Suna, and Çopur (2016) in apricots affected by a higher temperature and power level treatments caused less inhibition on DPPH radical.…”
Section: Determination Of Antioxidant Capacitysupporting
confidence: 91%
“…Control cheeses exhibited the highest (P < 0.05) h° values throughout the storage, followed by CS, whereas CIE presented the lowest (P < 0.05) h° values. The lower values observed in CIE and CM are due to higher a* values, which slightly distanced the hue angle results from 90° (yellow) and can be explained by extract interferences, probably by pequi carotene, which can lead to orange color variations (Ribeiro et al, 2014;Incedayi et al, 2016). Thus, all treatments are classified as white cheese by nearness to 90°.…”
mentioning
confidence: 86%
“…Hue angle values are expressed in degrees, starting at red (0°), with a gradual increase to yellow (90°), green (180°), and blue (270°). Regarding ΔE*, values were obtained by fluctuations in L*, a*, and b* values compared with the CC (Incedayi et al, 2016).…”
mentioning
confidence: 99%
“…This, in fact, corroborates the results previously reported in the literature where several bioactive compounds present in this fruit juice, including triterpénoïdes (cucurbitacins), carbohydrates, tannins, gum, peptides and leucoanthocyanins, were reported to enhance antioxidant activity (Attard & Attard, 2008;Bernard & Olayinka, 2010). Many researchers have shown that an increase in DPPH inhibition of radicals may be explained by several factors, such as the higher antioxidant power of polyphenols at an intermediate state of oxidation, the increase in reducing sugar and formation of Maillard reaction products, known to have a great antioxidant activity, which is often exerted in a chain-breaking and DPPH type mechanism (Madrau et al, 2009;Herch et al, 2014;İncedayi et al, 2016).…”
Section: Antioxidant Activities Of Extractsmentioning
confidence: 99%